Permanent First Molars Clinical Status among School Children Aged 8-12 Years in Kathmandu - Khapung, Anju; Rao, G. Nagaraja; Shrestha, Sujita (Journal of Nepalese Association of Pediatric Dentistry, 2020)
Introduction: Common oral diseases affecting school children are dental caries, gingivitis and malocclusion. Teeth mostly affected by dental caries in permanent dentition of children are the permanent first molars. Permanent first molars are key factors in occlusion and are most susceptible to dental caries. They maintain arch perimeter and provide best anchorage. Loss of these teeth leads to various problems like space management, tooth migration, problem in mastication and malocclusion.Objective: To assess the clinical status of first permanent molars among 8-12 year school children of Kathmandu.Methods: A cross-sectional study was done among 220 schoolchildren of age 8-12 years randomly selected from 2 private and 2 public schools of Kathmandu. Dental caries, gingival and oral hygiene status were measured by Decayed Missing Filled teeth (DMFT) index, Gingival index and Oral hygiene index-Simplified (OHI-S) respectively. Data was entered in Epidata 3.1 and analyzed in SPSS version 20.Results: The prevalence of dental caries in first permanent molars for study population was 54.5%. Mean DMFT score of first permanent molars was 0.96+1.2. Out of 867 molars examined, 197 (22.7%) were decayed. 98.5% of molars were erupted. Among the total study population, 184 (83.6%) had fair oral hygiene and 203 (83%) had gingivitis.Conclusions: This study shows the need to improve oral health status of first permanent molars of school children through promotion of dental health awareness and curative public health measures at school level.